Healthcare As a Universal Human Right : Sustainability in Global Health. - Nunes, Rui. (Taylor & Francis Group, 2022)
This important book outlines how, despite varying levels of global socio-economic development, governments around the world can guarantee their citizens' fundamental right to basic healthcare.